Effects of ω3 on Serum Level of Malondialdehyde and Homocysteine in Type 2 Diabetic Patients - M Jalali; SH Pouya; A Eshraghian; A Rajab; M Chamari; F Fatehi; M Zarei (Armaghane Danesh Bimonthly Journal, 2008)
ABSTRACT: